Pressure-Immobilization Bandages Delay Toxicity in a Porcine Model of Eastern Coral Snake ( Micrurus fulvius fulvius) Envenomation - German, Benjamin T.; Hack, Jason B.; Brewer, Kori; Meggs, William J. (Annals of emergency medicine, 2005)
Pressure-immobilization bandages are used in countries where neurotoxic snake envenomations are common. They impede lymphatic egress from the bite site and delay systemic venom toxicity. The effectiveness of these devices has not been evaluated in coral snake envenomations. We investigated the efficacy of pressure-immobilization bandages in delaying the onset of systemic toxicity in a porcine model of coral snake envenomation. A randomized controlled trial of pressure-immobilization bandages was conducted in a university animal care center. Subjects were 12 anesthetized, spontaneously breathing pigs, ranging from 9.1 to 11.4 kg. After injection with 10 mg of Micrurus fulvius fulvius venom in the subcutaneous tissue of the distal foreleg, subjects were randomized to receive no treatment or application of a pressure-immobilization bandage at 1 minute after injection. Treated animals had elastic bandages applied to the extremity and splinting for immobilization. Vital signs and quality of respirations were recorded. Outcome was the onset of respiratory failure or survival to 8 hours. Necropsies and histologic analysis of the envenomation site was performed. One animal from each group was removed because of the discovery of pre-existing respiratory pathology. Four of 5 pigs in the treatment group survived to 8 hours, but none in the control group survived. Mean time to onset of respiratory compromise was 170.4 ± 33.3 minutes in the control group. None of the pigs had histologic changes at the envenomation site consistent with ischemia or pressure-related injury. Pressure-immobilization bandages delayed the onset of systemic toxicity in our porcine model of M fulvius envenomation.